Gas Chromatography/Mass Spectrometry Method for Determination of Atenolol in Rabbit Plasma - Yilmaz, B.; Akba, V. (Asian Journal of Chemistry, 2010)
This work describes a gas chromatography/mass spectrometry (GC/MS) method with selectedion monitoring for determination of atenolol in rabbit plasma. Atenolol and internal standard metoprolol were extracted from plasma and cleaned up by using a single step liquid-liquid extraction. Calibration curves were linear over the concentration range 15-250 ng/mL. Intraand inter-day precision values for atenolol in rabbit plasma were less than 7.4 and accuracy (relative error) was better than 6.4. The analytical recovery of atenolol from rabbit plasma averaged out to 90.46 %. The limit of detection (LOD) and limit of quantification (LOQ) of atenolol were 5 and 15 ng/mL, respectively. The developed and validated GC/MS method was also successfully applied to a pharmacokinetic study of atenolol in New Zealand white rabbits.